2003
DOI: 10.1074/jbc.m304272200
|View full text |Cite
|
Sign up to set email alerts
|

L166P Mutant DJ-1, Causative for Recessive Parkinson's Disease, Is Degraded through the Ubiquitin-Proteasome System

Abstract: Mutations in a gene on chromosome 1, DJ-1, have been reported recently to be associated with recessive, earlyonset Parkinson's disease. While one mutation is a large deletion that is predicted to produce an effective knockout of the gene, the second is a point mutation, L166P, whose precise effects on protein function are unclear. In the present study, we show that L166P destabilizes DJ-1 protein and promotes its degradation through the ubiquitin-proteasome system. A double mutant (K130R, L166P) was more stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
182
4
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(201 citation statements)
references
References 36 publications
13
182
4
2
Order By: Relevance
“…By using gel filtration chromatography and co-immunoprecipitation analysis, we showed that DJ-1 exists as a dimer in solution, which is in agreement with recent reports (26,27,44). Our circular dichroism spectroscopic analyses revealed that, consistent with the crystal structure, the solution structure of DJ-1 contains substantial amount of ␣-helical structure.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…By using gel filtration chromatography and co-immunoprecipitation analysis, we showed that DJ-1 exists as a dimer in solution, which is in agreement with recent reports (26,27,44). Our circular dichroism spectroscopic analyses revealed that, consistent with the crystal structure, the solution structure of DJ-1 contains substantial amount of ␣-helical structure.…”
Section: Discussionsupporting
confidence: 79%
“…The ubiquitin-proteasome pathway consists of two major steps: the conjugation of ubiquitin to the substrate and subsequent degradation of the ubiquitinated substrate protein by the 26 S proteasome. Although the L166P mutant was recently suggested to undergo degradation by the ubiquitin-proteasome pathway (44), it remains to be determined experimentally whether the L166P mutant is indeed ubiquitinated. To address this issue, we used a well established in vivo ubiquitination assay (39,45) to measure the ubiquitination of DJ-1 and its L166P mutant in mammalian cells.…”
Section: Dj-1 Functions As a Cysteinementioning
confidence: 99%
“…61 The DJ1 mutations described are thought to affect either the active site or tertiary structure of the protein so as to reduce its half-life. 62 The mutations do not appear to modify its intracellular distribution. Cells lacking DJ1 were more sensitive to free radical damage and this was reversed by wild-type overexpression.…”
Section: Dj1 Mutationsmentioning
confidence: 98%
“…To further verify the interactions between DJ-1 and FADD, we performed co-immunoprecipitation experiments using human embryonic kidney 293 (HEK 293) cells ( Figure 4B) and H1299 cells ( Figure 4C). Transfection of cells with equal amounts of plasmids containing either wild-type DJ-1 or L166P usually results in a lower expression level of L166P compared with wild-type DJ-1 because of the instability of L166P (Macedo et al, 2003;Miller et al, 2003;Moore et al, 2003). Considering this problem, we transfected the cells with increased amounts L166P plasmids to elevate L166P levels as described previously (Junn et al, 2005).…”
Section: Dj-1 Does Not Function Downstream Of Caspase-8 Activationmentioning
confidence: 99%